The scoop - Michaels, Fern. (New York : Kensington Pub. Corp., 2009)
In this first book of a new series, Michaels introduces The Godmothers, four unforgettable women who are about to get a whole new lease on life.
Keywords: Mothers and daughters -- Fiction; Female friendship -- Fiction; Elderly women -- Fiction; Female friendship -- Fiction; Hollywood (Los Angeles, Calif.) -- Fiction; Love stories